Bioleaching rather than chemical conditioning using Fe[III]/CaO or polyacrylamide mitigates antibiotic resistance in sludge composting via pre-removing antibiotic resistance genes and limiting horizontal gene transfer. (1st January 2022) - Lu, Yi; Meng, Xiaoqing; Wang, Jiajun; Yorgan Dieketseng, Mahlatsi; Xiao, Yifan; Yan, Su; Chen, Yu; Zhou, Lixiang; Zheng, Guanyu
Graphical abstract: Highlights: Bioleaching conditioning mitigated ARGs in sludge compost products. Bioleaching conditioning led to the lowest abundances of ARG-associated bacteria. ARGs Shift during bioleached sludge composting can be ascribed to potential hosts. Pre-removal of ARGs is crucial for the ARGs reduction in bioleached sludge compost. Possible limited horizontal transfer of ARGs also contributed to their reduction. Abstract: Conditioning can drastically improve the dewaterability of sewage sludge and is widely practiced in most wastewater treatment plants (WWTPs). Sludge conditioning was also reported as a crucial step in sludge treatment to attenuate antibiotic resistance, but it remains unclear whether the attenuated antibiotic resistance by conditioning treatments would guarantee low abundance of antibiotic resistance genes (ARGs) in the compost products of municipal sewage sludge. Herein, the impacts of three conditioning treatments, including bioleaching and chemical conditioning using Fe[III]/CaO or polyacrylamide (PAM), on the abundances of 20 ARGs and 4 mobile genetic elements (MGEs) during conventional aerobic composting of dewatered sludge were investigated. It was found that the absolute and relative abundances of total ARGs in compost product of bioleached sludge accounted for only 13.8%-28.8% of that in compost products of un-conditioned, Fe[III]/CaO-conditioned, or PAM-conditioned sludges. Besides, bioleaching conditioning resulted in the lowest abundances of ARG subtypes and ARG-associated bacteria in the sludge compost product. The shift of ARG profiles in the bioleached sludge composting can be mainly ascribed to the ARG-associated bacteria, while the MGEs drove the ARG profiles during conventional composting of un-conditioned sludge and the two chemically conditioned sludge. Thus, bioleaching conditioning is superior to the chemical conditioning using Fe[III]/CaO or PAM in mitigating antibiotic resistance in sludge compost products, which was contributed by the pre-removal of ARGs prior to composting treatment and the potential limitation of ARGs transfer during conventional composting.